Investigation of the effect of impurity and surface defect in the sonocatalytic and photocatalytic degradation of methylene blue dye by TiO2 powder - Ayodeji Precious Ayanwale; Margarita Sánchez-Domínguez; Rodrigo Mayén Mondragón; Daniel Aguirre Aguirre; M. Navarrete (Results in Chemistry)
This study compares the performance of commercial titania (TiO2) powder in methylene blue (MB) dye removal in various solutions prepared using tap water (without and with a catalyst) under the same experimental conditions. Afterwards, the effect of impurities and surface defects is analyzed. From the result, low degradation percentage is obtained after sonolysis and photolysis while 50.1 and 97.8 % degradation is obtained after sonocatalysis and photocatalysis, respectively. Additional studies are done to provide information about the changes in the size, functional group, crystal structure, morphology, elemental composition, electronic structure and surface chemistry of TiO2 by using various analytical methods. The mean particle size obtained from DLS is 267 ± 8 μm before degradation, 342 ± 9 μm after sonocatalysis and 379 ± 11 μm after photocatalysis. From the FTIR analysis, MB is degraded into CO2 and H2O while XRD shows that anatase phase remains unchanged. SEM studies show no change after degradation. EDX and PL show the presence of impurities. XPS confirms defects and reveals the presence of carbonyl groups that are attributed to the oxidized by-products of MB. 75.4 % degradation after just 10 min of treatment shows that photocatalysis is the most effective way for removing MB dye. The formation of ozone (O3/UV-C), use of tap water and cheaper commercial titania powder have made the result from this study noteworthy, as it presents the same degradation percentage as those reported in literature that uses TiO2 nanoparticles.